The SsDREB Transcription Factor from the Succulent Halophyte Suaeda salsa Enhances Abiotic Stress Tolerance in Transgenic Tobacco - Xu Zhang; Xiaoxue Liu; Lei Wu; Guihong Yu; Xiue Wang; Hongxiang Ma (International Journal of Genomics)
Dehydration-responsive element-binding (DREB) transcription factor (TF) plays a key role for abiotic stress tolerance in plants. In this study, a novel cDNA encoding DREB transcription factor, designated SsDREB, was isolated from succulent halophyte Suaeda salsa. This protein was classified in the A-6 group of DREB subfamily based on multiple sequence alignments and phylogenetic characterization. Yeast one-hybrid assays showed that SsDREB protein specifically binds to the DRE sequence and could activate the expression of reporter genes in yeast, suggesting that the SsDREB protein was a CBF/DREB transcription factor. Real-time RT-PCR showed that SsDREB was significantly induced under salinity and drought stress. Overexpression of SsDREB cDNA in transgenic tobacco plants exhibited an improved salt and drought stress tolerance in comparison to the nontransformed controls. The transgenic plants revealed better growth, higher chlorophyll content, and net photosynthesis rate, as well as higher level of proline and soluble sugars. The semiquantitative PCR of transgenics showed higher expression of stress-responsive genes. These data suggest that the SsDREB transcription factor is involved in the regulation of salt stress tolerance in tobacco by the activation of different downstream gene expression.